The assessment and treatment of the musculoskeletal manifestations of cystinosis - Singh, Priya; Marsh, D’Arcy; Sharkey, Melinda (Frontiers in Nephrology, 2025)
Cystinosis is a rare autosomal recessive lysosomal storage disease caused by a defective lysosomal cystine carrier protein, cystinosin, resulting in formation and deposition of cystine crystals throughout the body. The renal manifestations of the disease have long been studied, but the musculoskeletal consequences of the disease are generally less well understood. Limb deformities, scoliosis, myopathy and low bone mineral density are associated with cystinosis and can lead to pain, fragility fractures, bone deformity, and difficulty ambulating. Although potentially exacerbated by renal disease and post-transplant medications, it has been found that the musculoskeletal manifestations of cystinosis are also due to inherent dysfunction caused by the mutation of cystinosin. Surgical intervention can provide solutions to the bony symptoms of cystinosis. Early referral to an orthopedic surgeon and evaluation for corrective scoliosis surgery, guided growth for growing children with lower extremity deformity and formal osteotomies for deformity correction in skeletally mature individuals may improve physical function and decrease pain. Standard principles of operative treatment of scoliosis and of bone deformity correction utilized for the treatment of bone deformity in other metabolic bone disease may be applied to patients with cystinosis in the absence of cystinosis-specific studies of the efficacy and outcomes of orthopedic surgery.